2015
DOI: 10.1111/cen.12739
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative follow‐up of Cushing's disease using cortisol, desmopressin and coupled dexamethasone‐desmopressin tests: a head‐to‐head comparison

Abstract: Adding the CDDT the first 3 years after surgery to immediate postsurgical cortisol evaluation should allow obtaining an optimal follow-up management of patients operated for Cushing's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…In the present study, we applied the criterion developed to diagnose patients with Cushing’s disease prior to surgery ( 8 ) to identify a response to desmopressin after surgery. This strategy is in line with other studies ( 20 , 38 ) and proved rational as patients in long-term remission presented a modest – if any – increase in ACTH upon desmopressin stimulation, well within the range observed in normal subjects. Indeed, ROC curve analysis and Youden’s index confirmed its good diagnostic effectiveness and superiority to percent ACTH increase.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we applied the criterion developed to diagnose patients with Cushing’s disease prior to surgery ( 8 ) to identify a response to desmopressin after surgery. This strategy is in line with other studies ( 20 , 38 ) and proved rational as patients in long-term remission presented a modest – if any – increase in ACTH upon desmopressin stimulation, well within the range observed in normal subjects. Indeed, ROC curve analysis and Youden’s index confirmed its good diagnostic effectiveness and superiority to percent ACTH increase.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, no specific cut-off could be identified; indeed, criteria for response varied from absolute cortisol increase over 7 µg/dL ( 23 ) to percentage ACTH and cortisol increase over 30% and 20%, respectively ( 20 ). Variants of desmopressin testing, i.e., dexamethasone-suppressed desmopressin stimulation, have also been proposed but again results proved promising though not fully predictive of surgical outcomes ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the loss of circadian rhythm (no clear definition is given) followed the positivity of CDDT in most patients. A subsequent study by the same group (94) reported similar performance of the DT and CDDT in the early postoperative period; during follow-up, however, the CDDT was more accurate in predicting the lack of recurrence (100% NPV), albeit with a worse positive predictive value, when performed in the first 3 years after surgery. Most importantly, as with DT, the positivity of CDDT was observed earlier than other markers of recurrence.…”
Section: Coupled Dexamethasone-desmopressin Test (Cddt)mentioning
confidence: 81%
“…The existing studies that assessed the usefulness of the DT in this regard are presented in Table 3. In these studies (92,93,94,95,96,97,98,99), the reported negative predictive value of the test ranges from 76 to 100%, being above 90% in the vast majority of the studies, whereas the sensitivity and specificity to detect recurrence vary greatly from 20 to 100% and from 57 to 100%, respectively. There is considerable disparity, however, among the studies with regards to the definition of response, the applied criteria for remission and recurrence and, the postoperative timing that the DT was performed.…”
Section: The Desmopressin Test In the Immediate Postoperative Period mentioning
confidence: 99%
See 1 more Smart Citation